Desain Lemari untuk Masjid di Kecamatan Cisaat Kabupaten Sukabumi - Dani Mardiyana; Lazuardi Akmal Islami; Zaid Sulaiman; Dodi Iwan Sumarno; Fabrobi Fazlur Ridha; Faturrohman Al-Ghozi; Reka Ramadhan (LPPM POLITEKNIK LP3I, 2024)
Cisaat Subdistrict has many mosques that are actively used by the community for various religious and social activities. However, based on an initial survey, it was found that many mosques in this area still lack adequate storage facilities to store various religious items such as Qur'ans, Islamic books, prayer garments (mukena), and sarongs. To address this need, the social service team designed a cabinet using a systematic and structured design method with a minimalist and ergonomic concept. The mosque cabinet design was created using Autodesk Inventor software with dimensions of 800 mm in length, 350 mm in width, and 1200 mm in height. The design for storing sarongs and prayer garments uses a closed concept (drawers), while the design for storing Islamic books and Qur'ans uses an open concept (shelves). Through this social service program, it is expected that an optimal design can be obtained to meet the cabinet needs of mosques in Cisaat Subdistrict, making this design a reference for mosque management committees in creating optimal and functional mosque cabinets.